Electrical and thermal efficiency of air-based photovoltaic thermal (PVT) systems: an overview - Nurul Shahirah Binti Rukman; Ahmad Fudholi; Ivan Taslim; Merita Ayu Indrianti; Intan Noviantari Manyoe; Uce Lestari; Kamaruzzaman Sopian (Institute of Advanced Engineering and Science, 2019)
The development of photovoltaic thermal (PVT) system is a very promising area of research. PVT systems using in various applications, such as solar drying, solar cooling, water heating, desalination, and pool heating. With the recognition of the potentials and contributions of PV system, considerable research has been conducted to attain the most advancement which may produce reliable and sustainable PVT system. The cooling system’s design refers to the absorber design which mostly focuses on water and air-based PVT systems. An air-based system has been developed through different absorber configurations, air flow modes and single- or double-pass design. Hence, a summarization on various research and development of air-based PVT system will be presented.